An exergy analysis of an air conditioning system - Muhamad, Pauziah; Darus, Amer Nordin (Universiti Teknologi Malaysia, 2003)
In today's modem building construction, air-conditioning system is almost a must. Even at it smallest component - the home, having the air condition installed is a great comfort; particularly in the tropics. It is due to its significant use that the air conditioning system is being selected as the subject of this study. Currently, the recognized methods in the study of energy conservation are the energy and the exergy methods, The home air conditioning unit is used to cool a space with effective temperature for human comfort at 25°C. In this study the behaviour of home air-conditioning unit using refrigerant R-134a has been investigated through the exergy method, Local ambient temperature used is 30°C. The challenge is to obtain quantitative information that will lead to a better understanding of the air conditioning irreversibility process and their distribution amongst the system component and minimizing them for optimal air conditioning cycle, In illustrating energy and availability analysis characteristic, the compressor work is altered through a pressure of 0.2 bar and was reduced from 2 bar to 1.8, 1.6, lA, 1.2 and eventually 1.0 bar. The greater the pressure difference which involved in the increase of the compressor work will lead to a higher rate of irreversibility. It is found that the evaporator and compressor loss contributed to the performance of the whole plant. The plant efficiency reduces about 52% when the inlet pressure at the compressor decreased from 2 bar to 1 bar. The greater the temperature difference between the evaporator and the cold room the higher is the irreversibility rate, Thus, the changes in temperature at the evaporator and pressure at the compressor contribute significantly to the plant irreversibility. Due to these phenomena there is a need for optimising the conditions imposed upon the evaporator and compressor